LSD1 inhibition attenuates targeted therapy-induced lineage plasticity in BRAF mutant colorectal cancer - Christopher A. Ladaika; Averi Chakraborty; Ashiq Masood; Galen Hostetter; Joo Mi Yi; Heather M. O’Hagan (Molecular Cancer)
Abstract Background BRAF activating mutations occur in approximately 10% of metastatic colorectal cancer (CRCs) and are associated with worse prognosis in part due to an inferior response to standard chemotherapy. Standard of care for patients with refractory metastatic BRAF V600E CRC is treatment with BRAF and EGFR inhibitors and recent FDA approval was given to use these inhibitors in combination with chemotherapy for patients with treatment naïve metastatic BRAF V600E CRC. Lineage plasticity to neuroendocrine cancer is an emerging mechanism of targeted therapy resistance in several cancer types. Enteroendocrine cells (EECs), the neuroendocrine cell of the intestine, are uniquely present in BRAF mutant CRC as compared to BRAF wildtype CRC. Methods BRAF plus EGFR inhibitor treatment induced changes in cell composition were determined by gene expression, imaging and single cell approaches in multiple models of BRAF mutant CRC. Furthermore, multiple clinically relevant inhibitors of the lysine demethylase LSD1 were tested to determine which inhibitor blocked the changes in cell composition. Results Combined BRAF and EGFR inhibition enriched for EECs in all BRAF mutant CRC models tested. Additionally, EECs and other secretory cell types were enriched in a subset of BRAF V600E CRC patient samples following targeted therapy. Importantly, inhibition of LSD1 with a clinically relevant inhibitor attenuated targeted therapy-induced EEC enrichment through blocking the interaction of LSD1, CoREST2 and STAT3. Conclusions Our findings that BRAF plus EGFR inhibition induces lineage plasticity in BRAF V600E CRC represents a new paradigm for how resistance to BRAF plus EGFR inhibition occurs. Additionally, our finding that LSD1 inhibition blocks lineage plasticity has the potential to improve responses to BRAF plus EGFR inhibitor therapy in patients.